2021
DOI: 10.1007/s10509-021-03974-y
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained spectral phenomena in the interstellar medium: an introduction

Abstract: There exists a number of astronomical spectral phenomena that have remained unidentified after decades of extensive observations. The diffuse interstellar bands, the 220 nm feature, unidentified infrared emission bands, extended red emissions, and 21 and 30 µm emission features are seen in a wide variety of astrophysical environments. The strengths of these features suggest that they originate from chemical compounds made of common elements, possibly organic in nature. The quest to understand how such organic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(40 reference statements)
0
4
0
2
Order By: Relevance
“…As ALMA and Rosina teams proposed, PH 3 can suffer sequential dissociations in the presence of UV radiation, forming P atoms (Figure ). Phosphorus atoms can collide with another species, leading to PO­( 2 Π) or PN­( 1 Σ + ) molecules previously detected in other systems. ,,,, Or can condensate, forming solid phosphorus particles, as observed in Jupiter’s atmosphere .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As ALMA and Rosina teams proposed, PH 3 can suffer sequential dissociations in the presence of UV radiation, forming P atoms (Figure ). Phosphorus atoms can collide with another species, leading to PO­( 2 Π) or PN­( 1 Σ + ) molecules previously detected in other systems. ,,,, Or can condensate, forming solid phosphorus particles, as observed in Jupiter’s atmosphere .…”
Section: Resultsmentioning
confidence: 88%
“…The second phosphorus compound detected in interstellar space was the CP radical, found in the circumstellar region around IRC+10216, a late-type evolved star . High-quality ultraviolet observations have confirmed that phosphorus is depleted by approximately a factor of 3 relative to its Solar System abundance in lines of sight containing warm, diffuse clouds and denser cold clouds. , Therefore, a significant fraction of interstellar phosphorus must be trapped in the grain phase. The phosphorus detection as part of the dust components in comet Halley corroborates the previous hypothesis …”
Section: Introductionmentioning
confidence: 99%
“…In our case, the virtual absence of external compacting pressure ( p ≪ 1 atm) in the interstellar medium that would promote the presence of distorted configurations, for example, nonplanar PAHs, solely governed by intramolecular attractions and repulsions, determines the proposition of the following mechanism of reaction to explain the formation of [26]­helicene using phenanthrene and n -butane as reactants. Phenanthrene and n -butane have been suggested as molecules present in interstellar environments. , As described in Figure , the postulated reaction mechanism for the formation of helicenes is based on the addition of n -butane units to positions 3 and 4 of a phenanthrene moiety. Because this consecutive addition occurs in an environment with extremely reduced pressure, the pattern would lead to the progressive formation of benzo­[ c ]­phenanthrene, dibenzo­[ c , g ]­phenanthrene, [6]­helicene, [7]­helicene, ..., [26]­helicene, and so forth.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Contudo, ao longo dos avanços dos estudos espectroscópicos no século XX, em grande parte ocasionados pela física quântica, contatou-se que a linha do nebúlio era uma linha proibida do Oxigênio ionizado (O++), que ficou conhecida como OIII. Essa linha espectral do Oxigênio ocorria apenas em condições muito específicas de nebulosas, nas quais a densidade era muito baixa (Kwok, 2021). Então, nesse caso, tem-se a descoberta de novo elemento químico (que seria o Y de Hanson), que depois foi entendido como uma linha espectral do Oxigênio, um elemento conhecido há bastante tempo pelos estudiosos (que seria o X descoberto).…”
Section: Uma Taxonomia De Norwood Hanson Para As Descobertas Científicasunclassified